Groundwater Quality and Public Health (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book attempts to provide a platform for researchers, policy makers, and engineers to share their latest thoughts and findings on groundwater quality and public health, as well as novel methods dealing with groundwater pollution. The chapters published in this book include the latest research results by world-renowned researchers, whose findings can benefit researchers, engineers, policy makers, and government officials in future groundwater quality research and policy making.